Evaluation of Chinese OFDI on Local Industrial Structure: A Case Study based on Countries along the “One Belt and One Road” - Li, Chenglong (International Journal of Social Sciences and Public Administration, 2024)
With the “One Belt and One Road Initiative” (BRI) initially launched in 2013, Chinese outward foreign direct investment (OFDI) has obtained a further growth, which has had an unavoidable effect on the local economic activities of recipient countries. In order to weigh the potential and long-term impact of Chinese OFDI on local economy, this paper determines to test the correlation between Chinese OFDI and changes on local industrial structure via establishing a series of indicator. Relying on the data from countries along BRI from 2013 to 2021, the paper obtain two conclusions: (1) Chinese OFDI affects and improve the industrial efficiency of countries along BRI. (2) There are not obvious evidences on the correlation between Chinese OFDI and the proportion of different industries and the rationalization of local industrial structure, which needs a extensive study.